(untitled) (Contemporary Central & East European Law, 2020)
This article considers the necessity of preparing a comprehensive study, over absolute refusal grounds pertaining to functional signs set in the EU trademark law, which would meet the business community’s need to register non-traditional trade marks. The study aims to define the exact scope of the aforementioned exclusions through objective criteria that can render them a workable tool, distinct from refusal grounds pertaining to distinctiveness, and able to solve problems of overlapping rights. As its specific research methodology, the study adopts comparative results coming from the US trade dress functionality doctrine, and a specific input offered from a ‘law and economics’ perspective, including competition rules related to market definition and substitutability of products.